Empowering Cadres in Information Management and Hypertension Control Through a Digital Application in Lempuing and Nusa Indah Villages, Bengkulu City - Hermansyah, Hermansyah; Nafratilova, Mercy; Wulandari, Dwi; Pudiarifanti, Nadia; Hariadi, Efrizon (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Hypertension remains a major public health problem that requires improved patient knowledge and consistent blood pressure monitoring. Digital applications offer opportunities to support information management and hypertension control at the community level.Aim: This program aimed to empower community health cadres in information management and hypertension control through the use of a digital application.Methods: The community service program involved 16 cadres and were conducted through health education (lectures and discussions) and hands-on training on digital application use. Knowledge was measured using a 10-item multiple-choice questionnaire (maximum score 100). Skills were assessed using an observation checklist. The intervention lasted one month.Results: The average knowledge score increased from 70 (pre-test) to 93 (post-test), representing a mean increase of 23 points. Cadres also demonstrated improved skills in operating the digital application.Conclusion: Cadre empowerment through education and digital application training successfully improved their knowledge and skills in hypertension information management and control. This program supports the strengthening of community-based hypertension prevention efforts.